Selection of metal ions in different valence states on sludge conditioning: Analysis of hydrophobicity and evaluation of resource recovery capacity. (December 2022) - Lin, Wei; Zeng, Jie; Zhang, Rourou; He, Xu; Nan, Jun; Li, Guibai; Ma, Jun; Ngo, Huu Hao; Ding, An
Abstract: In this study, we applied three types of metal ions in different valence states (Na +, Ca 2+ and Fe 3+ ) to compare their similarities and differences in adjusting sludge properties during the process of sludge conditioning. Under the same ion concentration, the addition of Na + had strong capacity on damaging α-helix structure with the improvement of sludge hydrophobicity. However, the reduced hydrophobic polysaccharide and the increased hydrophilic protein result in the improvement of sludge hydrophilicity under the addition of Ca 2+ and Fe 3+ . Meanwhile, three types of metal ions all had the better ability on damaging the two-dimension spatial structure of extracellular polymeric substance (EPS) protein due to the effective destruction of β-sheet. Additionally, the application of these three types of metal ions could achieve different resources (existed in sludge) recovery and enhance the value of sludge. This work will help us make a more correct choice when conditioning sludge with metal ions to meet actual needs. Graphical abstract: Unlabelled Image Highlights: Na + enhanced the hydrophobicity of sludge by efficient destruction of α-helix. Ca 2+ /Fe 3+ boosted sludge hydrophilicity due to the dual effects on EPSpr and EPSps . Na + has the potential on improving sludge dewatering and incineration abilities.